EVALUASI PEMBELAJARAN ONLINE SELAMA PANDEMI COVID-19 TERHADAP HASIL BELAJAR MAHASISWA KEPERAWATAN - Delly Arfa Syukrowardi; Dini Rachmaniah Hidayat (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. Internet-based e-learning during Covid-19 quarantine becomes a burden for nursing student due to practical skills courses are difficult to assess. However, on the other hand that situation improves their digital literacy. This study was aimed to investigate the effect of web-based e-learning during quarantine of covid-19 pandemic on grade point average (GPA) among nursing student of Faletehan University. Data used were GPA of first semester (before covid-19 quarantine) and second semester (after covid-19 quarantine). GPA of bachelor nursing student were taken from student who in the first year (n=138), second year (n=119) and third year (n=91) respectively. Using paired t-test analysis, this study showed that there were found significant differences of GPA between first semester and second semester. Student who in the first year (mean = -.33, SD = .30, p = .000), second year (mean = -.04, SD = .22, p = .026) and third year (mean = -.36, SD = .16, p = .000) showed escalation of GPA, while student who in the fourth year (mean = .79, SD = .09, p = .000) showed degradation of GPA. Online learning only effective in learning cognitive area, for nursing student who in the last year of study especially, the majority of courses are practice at laboratory and at ward which is not suitable using online learning. Educational institution needs to develop internet-based learning platform with technology such as case-based virtual reality to facilitate student to learn nursing practice.Keywords: covid-19, e-learning, GPA, nursing, student